Social mobility among the Malaysian land development settlers - Nor Azlili Hassan; Ummi Munirah Syuhada Mohamad Zan; Azlina Abdullah; Hairol Anuar Mak Din; Marzudi Md Yunus (Penerbit Universiti Kebangsaan Malaysia, 2023)
Social mobility is a process of change or movement of a person or a group, from one position to another, in society either within the generation itself (intrageneration) or between generations (intergeneration) towards a better position than before or vice versa. This article attempts to evaluate the social mobility that occurs among the first and second generations of land development settlers. The study involves two states namely Pahang and Johor with a total of 742 respondents consisting of the settlers. The sample was selected based on the group and the purposive sampling method. The findings of the study show that there is a process of social mobility that occurs in terms of the level of education, employment, and income among the first and second generations settlers. The education level of the intergenerational group was found to be vertical social mobility. These changes have also resulted in better second-generation jobs and monthly income. This study contributes to the corpus of sociology on social mobility in society. The success of intragenerational vertical social mobility shows that the development programs implemented by the government change the socio-economic status and increase the income of the settlers which further increases the level of development of the Malaysian economy.